PEMBERDAYAAN MASYARAKAT SENTRA MEBEL PEMKOT PASURUAN DENGAN POLINEMA TAHUN 2019 - Suselo Utoyo; Mohammad Abdullah Anshori; Luchis Rubianto; Ayu Sulasari; Noverita Wahyuningsih (Publisher UPT P2M Politeknik Negeri Malang, 2019)
Furniture from Pasuruan city especially Bukir sub-district Gadingrejo has long been known by the people of East Java with a cheap image and many choices. Related to cheap labor costs due to high price competition and mutually deadening among furniture craftsmen. The furniture craftsmen have not been able to manage marketing properly and establish good networking. Furniture manufacturing centers are spread across 8 sub-districts with 3,458 craftsmen. The craftsmen only make important items that are sold, without seeing whether the quality of the production is good or not. This condition makes the furniture industry not develop despite having skilled human resources in making furniture, so that the welfare of the furniture craftsmen cannot be lifted.The problems found were 1) the low work motivation of Bukir Pasuruan furniture craftsmen, 2) lack of knowledge about financial management, 3) poor management of marketing distribution and marketing networks. The solutions offered for the existing problems are as follows: 1) provide motivation and empowerment training for SMEs, 2) provide Financial Life Skill (FLS) training as an effort to improve financial management, 3) Business Model Canvas (BMC) training to identify nine supporting elements of development business, 4) providing business assistance and utilizing wood waste as a by-product.